Appropriate DevR (DosR)-Mediated Signaling Determines Transcriptional Response, Hypoxic Viability and Virulence of Mycobacterium tuberculosis - De Majumdar, Shyamasree; Vashist, Atul; Dhingra, Sakshi; Gupta, Rajesh; Singh, Alka; Challu, Vijay K.; Ramanathan, V. D.; Kumar, Prahlad; Tyagi, Jaya Sivaswami (PLOS ONE, 2012)
Background The DevR(DosR) regulon is implicated in hypoxic adaptation and virulence of Mycobacterium tuberculosis. The present study was designed to decipher the impact of perturbation in DevR-mediated signaling on these properties. Methodology/Principal Findings M. tb complemented (Comp) strains expressing different levels of DevR were constructed in Mut1* background (expressing DevR N-terminal domain in fusion with AphI (DevRN-Kan) and in Mut2ΔdevR background (deletion mutant). They were compared for their hypoxia adaptation and virulence properties. Diverse phenotypes were noted; basal level expression (∼5.3±2.3 µM) when induced to levels equivalent to WT levels (∼25.8±9.3 µM) was associated with robust DevR regulon induction and hypoxic adaptation (Comp 9* and 10*), whereas low-level expression (detectable at transcript level) as in Comp 11* and Comp15 was associated with an adaptation defect. Intermediate-level expression (∼3.3±1.2 µM) partially restored hypoxic adaptation functions in Comp2, but not in Comp1* bacteria that co-expressed DevRN-Kan. Comp* strains in Mut1* background also exhibited diverse virulence phenotypes; high/very low-level DevR expression was associated with virulence whereas intermediate-level expression was associated with low virulence. Transcription profiling and gene expression analysis revealed up-regulation of the phosphate starvation response (PSR) in Mut1* and Comp11* bacteria, but not in WT/Mut2ΔdevR/other Comp strains, indicating a plasticity in expression pathways that is determined by the magnitude of signaling perturbation through DevRN-Kan. Conclusions/Significance A minimum DevR concentration of ∼3.3±1.2 µM (as in Comp2 bacteria) is required to support HspX expression in the standing culture hypoxia model. The relative intracellular concentrations of DevR and DevRN-Kan appear to be critical for determining dormancy regulon induction, hypoxic adaptation and virulence. Dysregulated DevRN-Kan-mediated signaling selectively triggers the PSR in bacteria expressing no/very low level of DevR. Our findings illustrate the important role of appropriate two-component- mediated signaling in pathogen physiology and the resilience of bacteria when such signaling is perturbed.